2001
DOI: 10.1128/aac.45.9.2638-2642.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Mice with Clindamycin Improves Survival of Endotoxic Shock by Modulating the Release of Inflammatory Cytokines

Abstract: Suppression of endotoxin release and subsequent production of inflammatory cytokines is crucial in the treatment of septic shock. We investigated the effect of clindamycin (CLI) on endotoxic shock induced in mice by Escherichia coli lipopolysaccharide (LPS). Mice were treated with CLI (160 to 600 mg/kg) or saline and then injected with E. coli LPS and D-(؉)-galactosamine intraperitoneally 0.5 h after CLI administration. Pretreatment with CLI significantly improved survival in a dose-dependent manner (CLI, at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Effective management of these infections includes early and appropriate antimicrobial treatment, which could also impact the production of virulent toxins. Antibiotics are known to modulate immune functions during inflammation or serious infections (29), and different classes of antimicrobials have various effects (32). Antibiotics that inhibit protein synthesis may reduce toxin production while potent cell wall inhibitors stimulate an increase in toxin release; however, these observations in vitro are limited to subinhibitory concentrations (21,53).…”
Section: Discussionmentioning
confidence: 93%
“…Effective management of these infections includes early and appropriate antimicrobial treatment, which could also impact the production of virulent toxins. Antibiotics are known to modulate immune functions during inflammation or serious infections (29), and different classes of antimicrobials have various effects (32). Antibiotics that inhibit protein synthesis may reduce toxin production while potent cell wall inhibitors stimulate an increase in toxin release; however, these observations in vitro are limited to subinhibitory concentrations (21,53).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, these anticytokine effects on inflammatory cytokines have been studied at a molecular level (12,14,16). It was recently reported that clindamycin (CLI) reduces tumor necrosis factor alpha (TNF-␣) concentrations in lipopolysaccharide (LPS)-stimulated THP-1 cells (8) and that CLI decreases TNF-␣ and interleukin 1␤ (IL-1␤) concentrations and increases serum IL-6 concentrations, as well as reducing mortality in the mouse model (4). The present study showed the mechanism of modulation by CLI of inflammatory-cytokine production by LPS-stimulated macrophages, both in vitro and in vivo.…”
mentioning
confidence: 99%
“…[29][30][31] Taken together with the culture results, sustained delivery of clindamycin in infected defects both prevents progression to frank infection and restores or maintains the inflammatory cytokine profile seen in noninfected induced membranes. The continued inflammatory state seen in the +Inc/-Abx group is not a favorable state for the bone regeneration.…”
Section: Discussionmentioning
confidence: 99%